Differential uplift on the boundary between the Eastern and the Southern European Alps: Thermochronologic constraints from the Brenner Base Tunnel. (7th May 2019) - Klotz, Thomas; Pomella, Hannah; Reiser, Martin; Fügenschuh, Bernhard; Zattin, Massimiliano
Abstract: The Brenner Base Tunnel will connect Innsbruck (Austria) and Franzensfeste (Italy) by piercing two of the most important fault structures of the Alps: the Periadriatic fault system (PFS) and the Southern limit of Alpine metamorphism (SAM). (U‐Th)/He dating (apatite) and fission‐track analysis (apatite and zircon) on samples taken during excavation reveal a complex pattern of exhumation through time. The results yield temporal constraints for relative vertical block movement and fault activity. Furthermore, they indicate differential uplift of the northern block along the ~E–W striking PFS and allow locating the position of the SAM in the overtilted nappe stack south of the Tauern Window. Our data strongly support, for the first time, an ongoing north‐side‐up movement along this section of the PFS until at least the end of Miocene.